The basics of digital forensics the primer for getting started in digital forensics - Sammons, John (Syngress Media, 2015)
Provides a foundation for people new to the digital forensics field. This book teaches you how to conduct examinations by discussion what digital forensics is, the methodologies used, key tactical concepts, and the tools needed to perform examinations. Details on digital forensics for computers, networks, cell phones, GPS, the cloud, and the Internet are discussed
Includes bibliographic references and index
Keywords: Computer crimes / Investigation; Forensic sciences; Criminal investigation; Crime laboratories; Computerforensik